Alteration of quality attributes and shelf-life in strawberry (Fragaria × ananassa) fruits during storage as influenced by edible coatings - HAZARIKA, T K; LALRINFELI, LALRINFELI; LALTHANMUANI, LALTHANMUANI; LALCHHANMAWIA, JONATHAN; MANDAL, DEBASHIS (The Indian Journal of Agricultural Sciences, 2019)
The present investigation was carried out during 2015-16 at department of Horticulture, Aromatic and Medicinal Plants, Mizoram University, Aizawl to find out suitable edible coating on prolonging shelf-life of strawberry fruits.The different treatments were: T1: coconut oil 100%, T2 : castor oil 100%, T3 : olive oil 100%, T4 : Liquid paraffin wax 100%, T5 : Aloe vera gel, T6 :chitosan (1% w/v), T7 : chitosan (2%w/v), T8 : kaolene (1%w/v), T9 : kaolene (2%w/v), T10 : carboxy methyl cellulose (CMC) (1% w/v), and T11 : control (Water spray). The results revealed that among the different edible coatings studied, coating with coconut oil resulted lowest PLW (17.57%), maximum marketable fruits retained (56.67%), total sugars ( 8.82%), ascorbic acid (65.74 mg/100 ml juice), total anthocyanin content (33.38%) of fruits. The various quality parameters in terms of flavour, taste, appearance and overall acceptability were also found superior in this particular treatment.